Effects of the inclusion of a rumen-protected B-vitamin blend and hydroxy trace minerals in the diets of confined Nellore cattle on performance and cecal and ruminal histology - de Arruda, Maria Carolina Gonçalves [UNESP]; de Nazaré Santos Torres, Rodrigo [UNESP]; Rozza, Daniela Bernadete [UNESP]; Chardulo, Luis Arthur Loyola [UNESP]; Baldassini, Welder Angelo [UNESP]; Curi, Rogério Abdallah [UNESP]; Pereira, Guilherme Luis [UNESP]; de Farias, Iasmin Myrele Santos Calaça [UNESP]; Porcionato, Marco Aurélio; Neto, Otávio Rodrigues Machado [UNESP] (Elsevier, 2025)
Increasing grain inclusion in the diets of feedlot cattle is associated with elevated oxidative stress, which may affect performance and meat quality. In this context, the objective was to evaluate the effects of supplementing rumen-protected B-complex vitamins and hydroxy trace minerals (HTM), specifically Cu and Zn (VitB+HTM(Cu+Zn)), in the diets of confined Nellore cattle fed different starch levels on performance, carcass traits, meat quality, cecal histopathology, and rumen health. The experimental followed a randomized block design in a 2 × 2 factorial arrangement, with two factors: starch level (high or low) and the inclusion of VitB+HTM(Cu+Zn). The finishing period was divided into two phases. In the first phase (days 1–55) 120 Nellore bulls were allocated to two treatments: high starch (HS) and high starch with VitB+HTM(Cu+Zn) (HSVI). In the second phase (days 56–108), half of the animals were switched to a low-starch diet, resulting in four treatment groups: high starch (HS), high starch with VitB+HTM(Cu+Zn) (HSVI), low starch (LS), and low starch with VitB+HTM(Cu+Zn) (LSVI). The inclusion of VitB+HTM(Cu+Zn) had no effect (P > 0.05) on feed intake or performance during both the first phase (days 1–55) and the second phase (days 56–108) of feedlot finishing. However, over the entire finishing period (108 days), animals fed a high-starch diet showed improved feed efficiency (P = 0.010), increased thickness of the keratinized epithelium (P = 0.051), and reduced drip loss (P = 0.023) and cooking loss (P = 0.042) in meat, along with a reduction in papilla surface area (P = 0.001). The inclusion of VitB+HTM(Cu+Zn) in the diet increased papilla width (P = 0.051) in both high- and low-starch diets and improved meat color in animals fed low-starch diets. Supplementation with VitB+HTM(Cu+Zn) did not affect the histopathological parameters of the cecum in confined Nellore cattle fed diets with different levels of starch. However, VitB+HTM(Cu+Zn) supplementation improved meat quality in animals fed low-starch diets and enhanced rumen health in confined Nellore cattle.